Identidade ativista e autonomia: o Movimento de Resistência Global e a emancipação dos sujeitos em um mundo dominado - Campos, Alessandro de Oliveira (2007)
This dissertation investigates the identity of autonomous activists in the Global Resistance movement. We begin with a central category of Social Psychology, the conceptual use of identity-metamorphosis-emancipation sintagma. The proposal arose in the inquiry for the political Identity of the autonomous activist as a transformation process for the emancipation of the subject in a dominated world. This transformation occurs on the path to what we call Post-Conventional Identity. For this observation an analysis was performed of the history of the life of a member of the São Paulo Independent Media Center, as well as field work including participation in meetings and acts of autonomous nature. We perceive that nobody is born an activist, but passes through a process that leads him to this place. To think of the autonomous activist as a role is a contradiction, but to consider the activist identity as an I who searches for autonomy and recognizes the diverse actions for another political and social reality, which with new forms of existence come to gain legitimacy for the struggles in search of emancipation. The history of life of the autonomous activist passes through different processes that can take it to an amplification of given values and recognitions being more cooperation than competition. This work searches to weave reflections on the different possibilities to be political beyond the institutions and traditional parties